2006
DOI: 10.2520/myco.56.3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Isoterrein from Neosartorya fischeri

Abstract: In the screening for new antifungal substances from fungal sources against pathogenic filamentous fungi and yeasts, 1) two cyclopentanone derivatives, isoterrein (3) and terrein (4), were isolated along with the antifungal compounds, nortryptoquivalone (1), originally isolated from Aspergillus clavatus Desmazieres 2) , and aszonalenin (2), originally isolated from Aspergillus zonatus Kwon & Fennell 3) , from the chloroform-methanol (1:1) extract of Neosartorya fischeri (Wehmer) Malloch & Cain IFM52672. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 8 publications
1
21
0
Order By: Relevance
“…A literature search revealed that the NMR data of the isolated compound corresponded very well to those of acetylaszonalenin (3,4). Aszonalenin was previously isolated from another N. fischeri strain IFM52672 (7). MS data confirmed the structure of the isolated compound as acetylaszonalenin.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…A literature search revealed that the NMR data of the isolated compound corresponded very well to those of acetylaszonalenin (3,4). Aszonalenin was previously isolated from another N. fischeri strain IFM52672 (7). MS data confirmed the structure of the isolated compound as acetylaszonalenin.…”
Section: Resultsmentioning
confidence: 54%
“…Together with its non-acetylated form aszonalenin, it was also identified in various fungal strains, e.g. Aspergillus zonatus (4), Aspergillus fumigatus (5), Aspergillus carneus (6), and Neosartorya fischeri IFM52672 (7). Their stereoisomer epiaszonalenins A ( Fig.…”
Section: From the Philipps-universität Marburg Institut Für Pharmazementioning
confidence: 99%
“…Fungus A. terreus PT06-2 was incubated in a high-salt medium containing 10% salt and extracted with EtOAc to afford a crude extract. The crude extract (31.2 g) was separated by extensive chromatography using silica gel, Sephadex LH-20 and HPLC to give compounds 1 – 15 ( Figure 1 ), including three new compounds: terremides A and B ( 1 , 2 ), terrelactone ( 3 ), and twelve known ones: methyl 3,4,5-trimethoxy-2-(2-(nicotinamido)benzamido)benzoate ( 4 ) [ 15 ], (+)-butyrolactones I–III ( 5 – 7 ) [ 16 19 ], 3-hydroxy-5-[[4-hydroxy-3-(3-methyl-2-buten-1-yl)phenyl]methyl]-4-(4-hydroxyphenyl)-2(5 H )-furanone ( 8 ) [ 20 ], aspernolide A ( 9 ) [ 16 ], 5-[(3,4-dihydro-2,2-dimethyl-2 H -1-benzopyran-6-yl)-methyl]-3-hydroxy-4-(4-hydroxyphenyl)-2(5 H )-furanone ( 10 ) [ 18 ], territrem B ( 11 ) [ 22 ], (−)-(1 R ,4 R )-1,4-(2,3)-indomethane-1-methyl-2,4-dihydro-1 H -pyrazino[2,1- b ]quinazoline-3,6-dione ( 12 ) [ 23 ], R (−)-6-hydroxymellein ( 13 ) [ 24 ], trans -4,6-dihydroxymellein ( 14 ) [ 25 ], and (+)-terrein ( 15 ) [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chemical screening for A. terreus PT06-2 showed that the chemical diversity of the secondary metabolites is the richest at 10% salinity compared with those at 0% and 3% salt. Chemical investigation in 10% salinity resulted in isolation and identification of three new compounds, terremides A and B ( 1 , 2 ), terrelactone ( 3 ), along with twelve known compounds ( 4 – 15 ) [ 15 – 26 ]. Antibacterial activity of the new compound 2 against Enterobacter aerogenes , and the new compound 1 and 4 against Pseudomonas aeruginosa were observed.…”
Section: Introductionmentioning
confidence: 99%
“…6.1 and 6.4 ). Aszonalenin and its acetylated derivative acetylaszonalenin are produced by Aspergillus zonatus [ 57 ], A. fumigatus [ 58 ], A. carneus [ 59 ], and N. fi scheri NRRL 181 [ 60 ].…”
Section: The Biosynthesis Of Acetylaszonaleninmentioning
confidence: 99%